Environmental Changes in Eastern Lapland during the last 50 years - Folestad, Magdalena (Helsingin yliopisto, 2022)
The study is sought to study how and if the environment has changed in eastern Finnish Lapland in a long-term perspective. Variables related to the current state of the environment, are atmospheric composition and aerosols, meteorology, and biology. The study is based on measurements from Värriö Subarctic Research station for the years 1973 to 2021. Included in atmospheric composition, are the atmospheric anthropogenic gas concentrations of CO, NOx, O3 and SO2. SO2 is also used in a proxy to estimate H2SO4 concentrations. Decreasing long-term trends are found for CO, NOx, SO2 and H2SO4. The decreasing emissions from Kola peninsula, is the cause for long-term decrease of SO2, which result in decreasing H2SO4 concentrations. Results of particle size distribution show an increasing concentration of small particles and decrease of large particles. Decline of particles leads to less NPF, CCN and will resultingly influence cloud properties. Air temperature has increased 2.38 °C and snow cover days have decreased by three weeks, between 1975 and 2021. Snow depth and precipitation show less significant changes. Heat sum have from 1981 to 2021 increased with 247 °C days, indicating more active and growing trees. Birch leave development show indications of leave burst and developed leaves to occur at earlier date, over the years 1981-2021. Grouses, shorebirds, and cavity-nesters show large inter-annual variations. Some of the bird species appears to benefit from environmental changes while others appear to have difficulty adapting.